(untitled) (LEARNing Landscapes, 2016)
In this article, the authors2 examine the generative, yet heretofore under-articulated convergences and divergences between the eld of expressive arts (EXA) and the sub-genre of arts-based research known as a/r/tography. Experimenting with the discursive and practical terrain between the two elds, the authors discuss what they see and sense as the potentiality for an EXA-informed variant of a/r/tographic research informed by new materialist theoretical perspectives. Overall, the work aims to contribute to the expanding dialogue among arts-based researchers who are reaching across diverse discursive and disciplinary boundaries, mining relevant conceptual and practical linkages for thinking the role of creative making practices in social and educational inquiry anew.